Present status of participatory plant-breeding research on wheat at the National Wheat Research Program of Nepal - Bhatta, M.R.; Ortíz Ferrara, G.; Gurung, B.; Pokhrel, Thaneswar; Gautam, N.R.; Gurung, P.; Neupane, R.B. (CGIAR System-wide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovations, 2001)
Participatory varietal selection work in the form of coordinated farmers' field trials involving farmers, extension agents, and researchers has been a regular component of the wheat-improvement program of Nepal since the 1970s. In this system, varietal testing is carried out in farmers' fields, but the participation of farmers in actual breeding work has varied greatly. Recently, more farmer-collaborative plant breeding work has been initiated in the Bankatti village of the Rupandehi district a pre-breeding participatory assessment involving 20 male and female farmers was conducted to determine the preference criteria that farmers employ in sleeting for wheal varieties. There was some degree of variation in preference criteria listed by women and men farmers. Male and female farmers were allowed to select evaluate 12 wheat varieties grown in farmers' fields al near maturity, based on preference criteria set out during the pre-breeding exercise.